Effect of cold rolling on aging precipitation and mechanical properties of magnesium-aluminum alloy - Feiya Liu; Renlong Xin; Yiru Zhong; Qing Liu (Journal of Magnesium and Alloys)
Although magnesium-aluminum alloys, such as AZ80 and AZ91 have promising application potential in automotive, high-speed train and aerospace fields, their age-hardening response is generally not very appreciable. In this work, the aging-hardening response of AZ80 alloy was effectively enhanced by applying cold-rolling deformation before conducting conventional aging treatment at 200 °C. Compared to the directly aged sample, the yield strength of the pre-rolling and aged sample was increased by 35 MPa. Electron microscope examination confirmed that profuse {101¯1} and {101¯1}-{101¯2} twins, consisting of high density of dislocations and stacking faults, were generated by cold rolling. Blocky or ellipsoidal Mg17Al12 precipitates formed at the twin boundaries (TBs) during subsequent aging treatment. Crystallographic analysis indicated that the precipitates at {101¯1} TBs always held an identical Potter OR with both the matrix and twin, while the precipitates at {101¯1}-{101¯2} TBs exhibited three different ORs: Burgers OR, Potter OR and P-S OR with either the matrix or the twin. Moreover, recrystallized grains were found inside {101¯1}-{101¯2} double twins after peak-aging at 200 °C, implying that precipitation and recrystallization might occur concurrently along TBs at a relatively low temperature. It was speculated that the highly stored energy inside twins and the high elastic energy between the precipitates and twins were driving factors for the occurrence of recrystallization.